Understanding the Role of Trauma and Violence Exposure on Justice-Involved LGBTQA and GNC Youth in Hennepin County, Minnesota, 2018 - Hoffman, Andrea ([Verlag nicht ermittelbar], 2020)
The Hennepin County Department of Community Corrections and Rehabilitation Office of Policy, Planning and Evaluations surveyed 150 youth to examine the role of trauma and violence on justice-involved lesbian, gay, bisexual, transgender, questioning/unsure or asexual (LGBTQA) and gender non-conforming youth (GNC). Youth were surveyed and administrative human services and juvenile justice data were also analyzed. The correctional staff were surveyed with an organizational self-assessment on employee perceptions of trauma-informed practices and policies. A subset of youth (N = 60) were interviewed using the Juvenile Victimization Questionnaire Revised Version 2 (JVQ-R2) and the Adverse Childhood Experiences (ACEs) tool to assess trauma and victimization. This survey also collected demographic information as well as the participants' history of harassment, bullying, suspension, expulsion, housing arrangements, and foster care involvement.